A Sociological Analysis of The Main Characters in The Novel The Good Earth - Endah Alamsari Andayani (BADAN PENERBIT STIEPARI PRESS, 2023)
The purpose of the study is to analyze the main characters by collecting and choosing their actions, speech, and thoughts from the point of view of sociology. The approach is analytical (two methods: an extrinsic approach that deals with theories from some books, sociology ones, and an intrinsic approach that deals with elements in the Buck novel